2017
DOI: 10.1186/s40409-017-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive determinants of scorpion stings in a tropical zone of south Iran: use of mixed seasonal autoregressive moving average model

Abstract: Background: More than 1.2 million scorpion stings occur annually worldwide, particularly in tropical regions. In the absence of proper medical care, mortality due to venomous scorpion stings is an important public health issue. The aim of the present study is to explore the temporal trend of scorpionism with time series models and determine the effective factors on this event using regression models. Methods: A retrospective cross sectional study was conducted on 853 scorpion stung patients. They were referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
4
27
1
2
Order By: Relevance
“…Clinical symptoms and mortality from scorpion stings are related to two main factors: the characteristics of the stung patient (such as age and health condition) and the characteristics of the scorpion (such as species and venom potency) [ 77 , 119 , 120 ]. Scorpionism by Hemiscorpius is an important public health issue in Iran, especially in urban areas of the southwest and south regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical symptoms and mortality from scorpion stings are related to two main factors: the characteristics of the stung patient (such as age and health condition) and the characteristics of the scorpion (such as species and venom potency) [ 77 , 119 , 120 ]. Scorpionism by Hemiscorpius is an important public health issue in Iran, especially in urban areas of the southwest and south regions.…”
Section: Discussionmentioning
confidence: 99%
“…A positive significant correlation between the frequency of scorpion stings and the environment temperature as well as the sunshine duration was reported [ 73 ]. However, the correlation between stings and relative humidity as a climate factor was negative [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But assessing associated residual plot (graph not shown) revealed that there was a seasonal trend in the data. Although ACF and PACF for residual suggest an AR 1 model for seasonal trend, but in the ARMA × (1, 1) (1, 1) 12 model, AR 1 and SAR 12 were not significant (P = 0.276 and 0.831, respectively). Based on the corresponding RMSE value, the ARMA × (1, 0) (1, 1) 12 had the best fit for the available data and was thus considered the optimal model (Table 4).…”
Section: Time Series Model To Determine the Monthly Trend Of Snakebitesmentioning
confidence: 80%
“…This method is, however, unable to distinguish between the promastigote and amastigote forms of the parasite. The detection of L. major kDNA in wild sandflies of this region points to the increasing clinical significance of ZCL in recent years, in addition to the non-infectious (Ebrahimi et al 2017) and other infectious diseases (Fakoorziba et al 2006;Farhadpour et al 2016;Neghab et al 2006) in southern parts of Iran. Despite attempts to look for the presence of Crithidia parasite both in human lesion smears and naturally caught sandflies near rodent burrows and domestic settlements, no trace of its kDNA was discernible.…”
Section: Discussionmentioning
confidence: 96%